Descriptive study: assessment of perceived self-effectiveness in the feeding of university students - Degrave, Valentina M. (2021)
Introduction: Self-efficacy refers to personal ability to control one's own behavior, being able to adopt a beneficial behavior and stop practicing one that would be harmful. Its assessment as a tool in health field is becoming increasingly important. The objectives were assess perceived self-efficacy in university students related to eating behaviors considered healthy and determine possible differences between careers. Methods: A psychometric test of food self-efficacy was used, validated and adapted to the Argentine food culture. The instrument was made up of 20 items, with a response option according to the Likert scale (1: lack of ability; 5: being very capable), corresponding to 4 categories: high-fat foods; healthy food; sweet foods and healthy drinks. Participants included 300 students from 3 careers: Biochemistry (BQ) and Bachelor's degrees in Biotechnology (BB) and Nutrition (BN). Results: The reliability of the instrument was 0.83 (Cronbach's Alpha). Population included 80% women and 20% men, 21 ± 4 years old. The healthy drinks category received the highest score, without observing statistical differences between careers (4.47, 4.37 and 4.37). The score obtained by BN corresponds to a greater sense of perceived self-efficacy than BQ and BB (respectively) in: foods high in fat (3.76 vs 3.31 and 3.50; p=0.001); healthy food (4.23 vs 3.75 and 3.90 p=0.003) and sweet foods (3.71 vs 3.53 and 3.55; p=0.016). Conclusions: It is assumed that the assessment of self-efficacy is an important predictor of the actions of individuals in various situations, resulting in a valuable tool to elucidate the particularities and promote nutritional food education in university students of different careers.